The Religion Of Art, Art For Art’s Sake: Dante Gabriel Rossetti And Walter Pater - Cheeke, Stephen (Romanticism and Victorianism on the Net, 2011)
This article assesses the meaning of the phrase “the religion of art” in the nineteenth century, taking “art” to denote literature, painting and sculpture, and focuses this question in relation to two central ideas: to the Coleridgean “Symbol” (his famous tautegorical figure), and to the conceptual provenance and meaning of the phrase “art for art’s sake” (an apparent tautology). From the former it traces contrasting paths for the idea of the “translucence of the Eternal through and in the Temporal” (The Statesman’s Manual 30). One is via the “art for art’s sake” movement and aestheticism (with close attention to Walter Pater’s writings), drawing upon Romantic Hellenism in order to challenge Christian ideas of transcendence. The other is through the writings of Dante Gabriel Rossetti, in which a relationship is posited between the Victorian poet and his Catholic antitype. The religion of art as it manifested itself in the 1840s and 50s is, I shall argue, significantly different from the religion of art as it emerged in Paterian aestheticism later in the century.